Research in organizational change and development. Vol. 24 - Noumair, Debra Ann.; Shani, Abraham B. (Bingley, U.K. : Emerald, 2016)
Highlights include a reflection on forty years of collaboration and provides an inside perspective on collegial partnerships; the first recipients of the Pasmore-Woodman Award (AOM 2015) consider personal recollections as well as general principles about successful academic partnerships; one of the first women in the field provides a perspective on the interdependence of research and practice through a gender lens; while reflecting on the role of women in ODC across a fifty-year time period; strategies for managing changes in the research question when conducting field-based action research advances our understanding of evidence-based practice through the application of theory; Dialogic OD, a relatively new perspective in the field, is explored by discussing a case in which social space serves as transitional space and the ODC practitioner is provided a theoretically informed set of principles that can be applied and evaluated across contexts; the nature and role of organization identity shades new insights about the potential impact of organization development work on company culture and effectiveness; the challenges of integrating business strategy and organization development in the fast changing newspaper industry.
Working together revisited / Bob Hinings, Royston Greenwood -- Reflections on gender and organization development consultation / Barbara Bunker -- I never promised you a rose garden: when research questions ought to change / Robert MacIntosh, Jean Bartunek, Mamta Bhatt, Donald MacLean -- The perception of change strategy scale: validating the measure / David Szabla, William Dardick, Jennifer Devlin -- Social space as a genernative image for dialogical organization development / Victor Friedman, Israel Sykes, Noam Lapidot-Lefler, Noha Haj -- Organization identity: its role in organization change / Shannon Brown, Michael Manning, James Ludema -- Transformation in a tightly nested system: employing fast cycles of change / Tobias Fredberg, Johanna Pregmark -- To bankruptcy and back: turnaround strategies for firm emergence, long term survival, and speed / Ramkrishnan (Ram) V. Tenkasi, Yehia Kamel.
Includes bibliographical references.
Print version record
Keywords: Business & Economics -- Organizational Behavior; Organizational theory & behaviour; Organizational change